Internalisasi Nilai Religiusitas Melalui Film Laut Tengah dalam Pembelajaran Pendidikan Agama Islam di MTs Manbail Futuh 2 Bancar - Nisa Uzzaroh (Jurnal Budi Pekerti Agama Islam, 2025)
This study was motivated by the low level of internalisation of religious values in Islamic Religious Education, especially at the madrasah level, where the process of instilling valuesoften stops at the cognitive level. This study aims todescribe the process of internalising religious values through the film Laut Tengahand assess its effectiveness in improving students' understanding andappreciation of religious values at MTs Manbail Futuh 2 Bancar. The approach used was qualitative with a case study design, because the phenomenon under reviewwas contextual and required in-depth understanding. Datawere collected through direct observation during learning, interviews with teachers andstudents, as well as documentation of learning tools and film clips. Data analysiswas carried out through data condensation, data presentation, and drawingconclusions using the Miles, Huberman, and Saldaña model. The results showedthat the film Laut Tengahwas effective in facilitating the internalisation of religious values through the visual,emotional, and cognitive engagement of students. Students were able to identify values such ashonesty, patience, discipline, gratitude, and social awareness, anddemonstrated appreciation reflected in their self-reflections. With teacher guidance, films became a medium capable of connecting values with the real experiences ofstudents.